World Bank annual report 1976 - World Bank.; International Development Association; International Finance Corporation; Multilateral Investment Guarantee Agency (Washington, D.C. : World Bank, 1976)
The book contains the report of World Bank activities as it concerns channeling financial resources from developed countries to the developing world.
Title varies slightly.
usc 18/04/2019
Loans
Keywords: Economic assistance; Banks and banking, International; Finance; Economics